Prevalence Study of Gastrointestinal Helminth in Domestics Dogs (Canis Familiaris) Slaughtered in Selected Abattoirs in Plateau State, Nigeria - Chanding, Armstrong Yusuf; Umar, Yahaya Abdullahi; Tenshak, Tanko James; Ibrahim, Shuaibu (Open Science Journal, 2018)
Being that dogs are domestic animals to man, they are also consumed as meat. This study therefore aimed to determine the presence of gastrointestinal helminth of dogs in the two Local Government Areas of Plateau State, Nigeria namely Jos South and Pankshin and also to identify possible risk factors of zoonosis. Gastrointestinal content of 228 slaughtered dogs in abattoirs were selected randomly from Unguwarkare in Jos South and Kurum, in Pankshin LGAs. Samples were conveyed to the parasitological division of the National Veterinary Research Institute (N.V.R.I) Vom, Plateau State, Nigeria for analysis. The Post-mortem Differential Parasite Counts procedure as described by the Food and Agriculture Organization (FAO) was used for the analysis. Of the total 228 feacal samples analysed, 138 (60.53%) were positive for at least one of the intestinal parasites. Among the gastrointestinal helminth, Taenia pisiformis, Dipylidium caninum and Echinococusgranulosus were the cestodes recorded with prevalence of 36.84%, 12.72% and 1.75% respectively. Nematodes recorded were Ancylostoma caninum (3.51%), Toxocaracanis (4.83%) and Trichurisvulpis(0.88%). However, from the 114 samples collected from Unguwarkare study area, 77(67.54%) were positive for the various intestinal helminthes which include Taenia spp. (42.98%), D. caninum (1316%) and E. granulosus (2.63%). As for the nematodes, A. caninum, T. canis and T. vulpis recorded 3.51%, 2.63% and 0.88% prevalences respectively. The parasites recorded from the remaining 114 samples analysed at Kurum include 28.95% T. pisiformis, 12.28% D. caninum and 0.88% E. granulosus while the nematodes recorded wereT. Canis (7.02%), A. caninum (3.51%) and T. vulpis (0.88%). The study revealed the presence of zoonotic gastrointestinal helminthes in dogs in the study areas with highest infection rate recorded at Unguwarkare in Jos South LGA compared with those of Kurum community of Pankshin LGA. Therefore, the general public in the said areas are at high risk of being infected with any of the zoonotic parasites.